2009
DOI: 10.1371/journal.ppat.1000270
|View full text |Cite
|
Sign up to set email alerts
|

Rab11A-Controlled Assembly of the Inner Membrane Complex Is Required for Completion of Apicomplexan Cytokinesis

Abstract: The final step during cell division is the separation of daughter cells, a process that requires the coordinated delivery and assembly of new membrane to the cleavage furrow. While most eukaryotic cells replicate by binary fission, replication of apicomplexan parasites involves the assembly of daughters (merozoites/tachyzoites) within the mother cell, using the so-called Inner Membrane Complex (IMC) as a scaffold. After de novo synthesis of the IMC and biogenesis or segregation of new organelles, daughters bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
149
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(161 citation statements)
references
References 58 publications
12
149
0
Order By: Relevance
“…The delivery of new plasma membrane for furrow formation relies on the Rab11A-mediated secretory vesicle transport, which is also responsible for delivering GAP45 (AgopNersesian et al, 2009). Interestingly, ablation of Rab11A function results in incomplete pellicle assembly in the inner regions between daughter cells, leading to a cell separation block late in the cytokinesis, with the formation of masses of multiple daughter cells (Agop-Nersesian et al, 2009), which is similar to the phenotype of FASII disruption reported here. Overall, our combined observations suggest that tethered daughter cells resulting from FASII disruption had matured, and that the division defect exhibited by these cells represents a specific failure in assembly of the daughter cell pellicle at the final step of cytokinesis.…”
Section: Discussionsupporting
confidence: 67%
“…The delivery of new plasma membrane for furrow formation relies on the Rab11A-mediated secretory vesicle transport, which is also responsible for delivering GAP45 (AgopNersesian et al, 2009). Interestingly, ablation of Rab11A function results in incomplete pellicle assembly in the inner regions between daughter cells, leading to a cell separation block late in the cytokinesis, with the formation of masses of multiple daughter cells (Agop-Nersesian et al, 2009), which is similar to the phenotype of FASII disruption reported here. Overall, our combined observations suggest that tethered daughter cells resulting from FASII disruption had matured, and that the division defect exhibited by these cells represents a specific failure in assembly of the daughter cell pellicle at the final step of cytokinesis.…”
Section: Discussionsupporting
confidence: 67%
“…Recent studies showed that Rab11 is required for the formation of the cleavage furrow, or contractile ring, for separation of the two daughter cells in cytokinesis (43)(44)(45)(46). Although it has been thought that the membrane is likely from the endosomes, as Rab11 is located on both endosome and TGN membranes, it is unclear whether the Golgi can also provide the required membranes for cytokinesis.…”
Section: Discussionmentioning
confidence: 99%
“…The apicomplexan parasite Trypanosoma brucei, the causative agent of African sleeping sickness, has also been shown to depend on PI4KIIIβ, as RNAi depletion of PI4KIIIβ in T. brucei resulted in inhibited growth accompanied with a distorted Golgi apparatus, mis-localized lysosomal proteins, distorted cell shape and improper cytokinesis [59]. Completion of Apicomplexan cytokinesis is also dependent on functional Rab11a assembly of the inner membrane complex [60]. Key to successfully targeting the parasite forms of PI4K will be the development of potent and specific inhibitors that do not target the human PI4Ks.…”
Section: Misregulation Of Type III Pi4ks In Diseasementioning
confidence: 99%